PROBLEMS AND PROSPECTS OF IMPROVEMENT OF REGIONAL MARKETING STRATEGY IN THE SPHERE OF MODERN EDUCATIONAL SERVICES - Водолазская, Наталия Владимировна (Eastern-European Journal of Enterprise Technologies, 2013)
One of the most rapid growing and perspective spheres of economy is education which is inseparably linked with providing of educational services. However actively going commercialization of education creates special difficulties for a marketing approach in the sphere of educational services and leads to the emergence of such problems as: - implementation of practice of admitting to the higher education establishments of the significant number of inappropriately prepared entrants, in connection with the reduction of their quantity because of the demographic crisis of the 90th years of the last century; - many higher educational establishments aren’t capable to support a high level of their teacher’s staff, in connection with the restriction of the possibility of the constant increase of its qualification in leading higher education establishments of the country and an exchange of experience. - the financial problems arising in higher education establishments, but put the brake on carrying out scientific research, in particular, directed to the strategic research of a situation the market of educational services. For increase of a rating of higher education establishment and efficiency of their own activity, nowdays educational establishments can use four versions of marketing activity: administrative marketing; marketing of partnership; internal marketing; communicative marketing.